2013
DOI: 10.1017/s0022029913000150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high pressure on the structure and antibacterial activity of bovine lactoferrin treated in different media

Abstract: The effect of high-pressure treatment (400, 500 and 650 MPa) on the structure and activity of bovine lactoferrin in different iron-saturation forms has been studied by several techniques. The structural changes produced in lactoferrin by high-pressure were analysed by differential scanning calorimetry and fluorescence spectroscopy, and the immunoreactivity by ELISA. The effect of high-pressure was also studied on some biological properties of lactoferrin, such as iron binding capacity, retention of the bound i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Thus, the composition of the secondary structure of bLF may vary with regard to the applied method of heat treatment. The temperature of denaturation and enthalpy change of denaturation of holo-LF is much higher than that of apo-LF, which suggests greater thermal resistance of iron-saturated forms of protein. , Application of high hydrostatic pressure as and alternative to heat treatment also confirmed much evident conformation stability of iron-saturated LF at extreme conditions compared to metal unsaturated LF …”
Section: Factors Affecting Lf Stabilitymentioning
confidence: 90%
See 1 more Smart Citation
“…Thus, the composition of the secondary structure of bLF may vary with regard to the applied method of heat treatment. The temperature of denaturation and enthalpy change of denaturation of holo-LF is much higher than that of apo-LF, which suggests greater thermal resistance of iron-saturated forms of protein. , Application of high hydrostatic pressure as and alternative to heat treatment also confirmed much evident conformation stability of iron-saturated LF at extreme conditions compared to metal unsaturated LF …”
Section: Factors Affecting Lf Stabilitymentioning
confidence: 90%
“…19,73 Application of high hydrostatic pressure as and alternative to heat treatment also confirmed much evident conformation stability of iron-saturated LF at extreme conditions compared to metal unsaturated LF. 74 Interestingly, relatively low temperatures are also capable of modifying protein biological functions. It was observed that LF storage of at 20 °C for 6 months significantly influenced the protein immunomodulatory function.…”
Section: Electrodialysis With Filtration Membranementioning
confidence: 99%
“…Mazri et al (2012) observed that the denaturation rate of LFb under HHP treatment (450-700 MPa/20 • C/0-40 min) was the lowest in phosphate-buffered saline (PBS), followed by bovine milk and whey. However, Franco et al (2013) reported that HHP at 500 MPa (20 • C/15 min) caused a greater loss of LFb in milk than in PBS and whey. They also found out that the antimicrobial activity of LFb in its apo and native forms was maintained well in PBS after HHP treatment at 400 MPa but was completely lost after 500 MPa treatment (Franco et al, 2013).…”
Section: Impact Of Hhp On Antimicrobial Proteinsmentioning
confidence: 97%
“…(2013) reported that HHP at 500 MPa (20°C/15 min) caused a greater loss of LFb in milk than in PBS and whey. They also found out that the antimicrobial activity of LFb in its apo and native forms was maintained well in PBS after HHP treatment at 400 MPa but was completely lost after 500 MPa treatment (Franco et al., 2013).…”
Section: Effects Of Hhp On Protein Nutritional Propertiesmentioning
confidence: 99%
“…In addition, pressure influences the lactoferrin structure and activity, its antimicrobial properties and ability to bind and hold iron. Under the action of 400 MPa, the lactoferrin structure does not change significantly, but treatment under 500 MPa and higher strongly affects LF properties, reduces its antimicrobial action [21]. For these reasons, the combined treatment of chicken breasts was used in the study.…”
Section: The Use Of Lactoferrin In the Food Industrymentioning
confidence: 99%